2019
DOI: 10.3390/ijerph16030464
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and Urban Environments

Abstract: Obesity is a major public health issue, affecting both developed and developing societies. Obesity increases the risk for heart disease, stroke, some cancers, and type II diabetes. While individual behaviours are important risk factors, impacts on obesity and overweight of the urban physical and social environment have figured large in the recent epidemiological literature, though evidence is incomplete and from a limited range of countries. Prominent among identified environmental influences are urban layout … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
36
1
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(41 citation statements)
references
References 53 publications
0
36
1
4
Order By: Relevance
“…Previous studies have indicated that PHNs working for local municipalities do not perceive hereditary diseases as genetic disorders caused by defective genes, but as a phenomenon caused by environmental and social factors shared among members of the community and family [ 19 ]. In fact, many previous studies have found that risk of cardiometabolic diseases (e.g., obesity, hypertension) varies depending on the geographical area [ 24 , 35 ], socioeconomic status [ 36 ], and environment [ 37 ]; in other words, members from the same community may be exposed to the same environmental and/or socioeconomic factors due to living in the same area and abiding by the same culture and lifestyle, and may even develop the same diseases. Consequently, even if concerns are potentially related to genetics (i.e., heredity and family history), PHNs might not perceive consulted symptoms as genetic disorders per se, but rather as products of complex environmental and socioeconomic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have indicated that PHNs working for local municipalities do not perceive hereditary diseases as genetic disorders caused by defective genes, but as a phenomenon caused by environmental and social factors shared among members of the community and family [ 19 ]. In fact, many previous studies have found that risk of cardiometabolic diseases (e.g., obesity, hypertension) varies depending on the geographical area [ 24 , 35 ], socioeconomic status [ 36 ], and environment [ 37 ]; in other words, members from the same community may be exposed to the same environmental and/or socioeconomic factors due to living in the same area and abiding by the same culture and lifestyle, and may even develop the same diseases. Consequently, even if concerns are potentially related to genetics (i.e., heredity and family history), PHNs might not perceive consulted symptoms as genetic disorders per se, but rather as products of complex environmental and socioeconomic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The driving forces are multifaceted, including changes in dietary and physical activity patterns related to transitions in livelihoods; moving from traditional food systems dependent upon subsistence farming to dependence upon income generation and the market [ 1 ]. These transitions are more prominent in transient urban settings where they contribute to an excess intake of energy, insufficient amounts of micro-nutrients and limited physical activity [ 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Changes in adiposity were classified according to relevant changes (i.e., Cohen’s d), which avoids a substantial loss of information in comparison with traditional overweight/obese classifications and provides information about the interindividual variation in our sample [ 38 ]. We provided a multidimensional perspective on this research topic by integrating a wide variety of intrapersonal, built environmental, and PA and sedentary behavior variables together that have been related to adiposity gain [ 51 ]. Our homogeneous sample of older women allowed us to focus on a population that has received less attention in the literature and that is experiencing a worrying increase in adiposity [ 52 ].…”
Section: Discussionmentioning
confidence: 99%